Anti-static antibacterial polypropylene composite membrane material and preparation method thereof
The preparation of polyketone nanofiber films loaded with silver nanoparticles and hot-pressing molding of polypropylene films through electrospinning has solved the shortcomings of the existing antibacterial polypropylene film materials in antibacterial efficiency, mechanical properties and antistatic functions, and achieved efficient and low-cost antistatic effect.
Patent Information
- Application Number
- CN202411721274.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing antibacterial polypropylene film materials have shortcomings in antibacterial efficiency, mechanical properties and antistatic functions, and it is difficult to meet the high requirements of food packaging and medical supplies for antibacterial and antistatic.
Polyketone nanofiber membranes were prepared by electrospinning, and silver nanoparticles were loaded with silver nitrate. The anti-electrostatic antibacterial polypropylene composite membrane material was prepared by hot pressing.
It significantly improves the antibacterial efficiency, barrier properties and impact resistance of polypropylene composite film materials, and also has anti-static functions, reducing the amount of silver nanoparticles and reducing production costs.
Smart Images

Figure CN119550665A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane materials, and in particular relates to an antistatic and antibacterial polypropylene composite membrane material and a preparation method thereof. Background Art
[0002] Polypropylene film materials are widely used in many fields such as food packaging, medical supplies, agricultural mulch, and building waterproofing due to their excellent mechanical properties, low density, and corrosion resistance. In the field of food packaging and medical supplies, higher requirements are also placed on the antibacterial properties of polypropylene film materials. The so-called antibacterial polypropylene film is to inhibit the proliferation or killing of microorganisms such as bacteria, molds, algae, and even viruses by adding antibacterial agents, thereby keeping itself clean. The use of antibacterial polypropylene film in food packaging can effectively prevent food from being contaminated by microorganisms during storage and transportation, and ensure the safety and hygiene of food; in terms of medical supplies, antibacterial polypropylene film is used to make packaging for medical devices and medical supplies, which can reduce the risk of cross-infection in hospitals; using it for drug packaging can protect drugs from microbial contamination and ensure the safety and effectiveness of drugs. In addition, for food and pharmaceutical products, static electricity may absorb pollutants such as dust and bacteria in the air, thereby contaminating the product, and may also cause adhesion, curling or deformation of plastic packaging films, thereby affecting the integrity and sealing of the packaging. Under certain conditions, static electricity may cause sparks, leading to safety accidents such as fire or explosion. Therefore, if the polypropylene film material can be given good antibacterial properties and antistatic function at the same time, the application value of the polypropylene film material will be greatly improved.
[0003] At present, the preparation of antibacterial polypropylene film materials is mainly achieved through the following methods.
[0004] (1) Blending method: The antimicrobial agent is mixed evenly with the polymer material, and then the antimicrobial film is made by extrusion, injection molding and other processes. This method is simple and easy, and the antimicrobial agent is evenly distributed, but the mechanical properties of the material may deteriorate, and the antimicrobial efficiency is not high.
[0005] (2) Surface modification method: Introducing antibacterial groups or coatings on the surface of polymer membranes by physical or chemical methods to give them antibacterial properties. This method does not change the internal structure of the membrane, but the interface strength and wear resistance of the surface antibacterial layer are not high, which makes it easy to fall off or wear, making it difficult for the antibacterial effect to last.
[0006] (3) Nanocomposite method: The nano antibacterial agent is dispersed in a polymer matrix to form a nanocomposite material. This method has a long-lasting antibacterial effect, but the preparation process is relatively complicated, and the antibacterial efficiency is low because the nano antibacterial agent is dispersed throughout the matrix.
[0007] Therefore, it is necessary to develop a polypropylene film material with a small amount of antibacterial agent added, high antibacterial efficiency, low production cost, good mechanical properties and antistatic function. Summary of the invention
[0008] In view of the above-mentioned defects of the prior art, the present invention provides an antistatic and antibacterial polypropylene composite film material and a preparation method thereof.
[0009] The technical solution adopted by the present invention to solve its technical problem is:
[0010] In a first aspect, the present invention provides a method for preparing an antistatic and antibacterial polypropylene composite film material, comprising the following steps:
[0011] a. preparing a polyketone spinning solution and obtaining a polyketone nanofiber membrane by electrospinning;
[0012] b. using polydopamine and silver nitrate to modify the polyketone nanofiber membrane to obtain a modified polyketone nanofiber membrane loaded with silver nanoparticles;
[0013] c. Place the polypropylene pellets into the mold frame and heat press them into a polypropylene film;
[0014] d. The modified polyketone nanofiber membrane loaded with silver nanoparticles is stacked on the polypropylene film, and then placed together in a mold frame, hot pressed at 180-200°C under a pressure of 5-10 MPa for 8-15 min, and then cold pressed at room temperature under a pressure of 5-10 MPa for 3-10 min, and then taken out to obtain an antistatic and antibacterial polypropylene composite membrane material.
[0015] In the above preparation method, in step a, hexafluoroisopropanol and dichloromethane are prepared into a mixed solvent in proportion, polyketone, dopamine and sodium chloride are added in sequence, the mixture is sealed and fully stirred at room temperature until the polyketone is completely dissolved, and the polyketone spinning solution is obtained after standing.
[0016] Furthermore, the mass ratio of hexafluoroisopropanol to dichloromethane in the mixed solvent is 1:(0.25-4); the mass ratio of polyketone to the mixed solvent is 1:(10-50); the mass ratio of polyketone to dopamine is 1:(0.05-0.2); and the mass ratio of polyketone to sodium chloride is 1:(0.005-0.02).
[0017] Furthermore, the polyketone is an aliphatic polyketone, which is a linear alternating copolymer synthesized from carbon monoxide, ethylene and propylene, and has a number average molecular weight of 90,000 to 120,000 g / mol.
[0018] In the above preparation method, in step b, the modification method is specifically:
[0019] b1. The tris(hydroxymethyl)aminomethane was dissolved in deionized water, and hydrochloric acid solution was added to adjust the pH to 8.5, and then the polyketone nanofiber membrane was fully immersed in the reaction. After the reaction was completed, the membrane was removed and dried to obtain a polydopamine-modified polyketone nanofiber membrane;
[0020] b2. Dissolve silver nitrate in deionized water, add ammonia water for sufficient reaction, then put in the polydopamine-modified polyketone nanofiber membrane and soak it thoroughly, then add appropriate amount of NaOH solution and glucose solution to continue the reaction. After the reaction is completed, take out the membrane and dry it to obtain a modified polyketone nanofiber membrane loaded with silver nanoparticles.
[0021] Furthermore, in step b2, the mass ratio of deionized water to silver nitrate is 1:(0.01-0.05); ammonia water is added dropwise for sufficient reaction, and the addition is stopped after the solution changes from clear to reddish brown and then to clear; the mass ratio of silver nitrate to NaOH is 1:(0.2-0.5); the mass ratio of silver nitrate to glucose is 1:(2-5); and the mass ratio of polyketone to silver nanoparticles in step a is 1:(1-5).
[0022] In the above preparation method, in step c, the mold frame is a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm; the mass ratio of the polypropylene pellets to the polyketone in step a is 1:(0.05-0.15).
[0023] Furthermore, the polypropylene pellets are polypropylene resins for film, and have a number average molecular weight of 50,000 to 150,000 g / mol, a melting point of 162 to 168° C., and a melt flow index of 2.8 to 30 g / 10 min (230° C. / 2.16 kg).
[0024] In the above preparation method, in step d, the mold frame is a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm; the mass ratio of the polypropylene film to the modified polyketone nanofiber membrane loaded with silver nanoparticles is 1:(0.01-0.9).
[0025] In a second aspect, the present invention provides an antistatic and antibacterial polypropylene composite film material prepared by the above preparation method.
[0026] The beneficial effects of the present invention are as follows: the present invention selects aliphatic polyketone as the modified resin film material, and aliphatic polyketone is a ketone-containing olefin-like polymer material, which has the advantages of high barrier, high impact resistance, high temperature resistance, chemical corrosion resistance, wear resistance, etc., and is similar to the molecular chain structure of polypropylene, and has good interface compatibility when the polyketone film layer and the polypropylene film layer are hot-pressed. More importantly, the polyketone nanofiber film can be formed into a dense polyketone film through a strictly defined hot-pressing molding process, and the film layer has excellent barrier properties, and the interface between the polypropylene layer and the polypropylene layer is tightly combined, which can significantly improve the barrier properties and impact toughness of the polypropylene composite film material. The polyketone nanofiber film prepared by a specific electrostatic spinning process has the advantages of high specific surface area and strong adsorption, and can realize the firm loading and uniform dispersion of silver nanoparticles on the polyketone film, while giving the composite film good antibacterial properties, it can also be antistatic. The present invention significantly improves the antibacterial efficiency, barrier properties and impact resistance of the polypropylene composite film material, and also has an antistatic function, while reducing the amount of silver nanoparticles added in the composite film, effectively reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a SEM image of the modified polyketone electrospun membrane loaded with silver nanoparticles in Example 1;
[0028] Figure 2 This is a SEM energy spectrum scanning image of the modified polyketone electrospun membrane loaded with silver nanoparticles in Example 1;
[0029] Figure 3 This is a SEM image of the cross section of the antistatic and antibacterial polypropylene composite film prepared in Example 1. DETAILED DESCRIPTION
[0030] The technical solution of the present invention can be specifically implemented in the following manner.
[0031] The antistatic and antibacterial polypropylene composite film material provided by the invention comprises a polypropylene film and a polyketone film stacked on the polypropylene film, wherein the interface between the polyketone film layer and the polypropylene film layer is tightly combined; the polyketone film is a dense modified polyketone nanofiber film loaded with silver nanoparticles.
[0032] The present invention provides a method for preparing the above-mentioned antistatic and antibacterial polypropylene composite film material, comprising the following steps:
[0033] (1) preparing a mixed solvent of hexafluoroisopropanol and dichloromethane in a mass ratio of 1:(0.25-4), adding polyketone, dopamine and sodium chloride in sequence, sealing and fully stirring at room temperature until the polyketone is completely dissolved, and standing to obtain a polyketone spinning solution;
[0034] The mass ratio of polyketone to the mixed solvent is 1:(10-50), the mass ratio of polyketone to dopamine is 1:(0.05-0.2), and the mass ratio of polyketone to sodium chloride is 1:(0.005-0.02);
[0035] The polyketone is an aliphatic polyketone, which is a linear alternating copolymer synthesized from carbon monoxide, ethylene and propylene, and has a number average molecular weight of 90,000 to 120,000 g / mol.
[0036] (2) spinning the polyketone spinning solution into a film through an electrospinning machine, removing the spun polyketone nanofiber membrane together with the silicone oil paper from the drum after spinning, removing the polyketone nanofiber membrane from the silicone oil paper after standing for 1 to 3 hours, placing it in a plate, transferring it to an oven at 80 to 100° C. and drying it for 12 to 18 hours to obtain a polyketone nanofiber membrane;
[0037] Among them, the specific process of electrospinning is: use the syringe barrel of the electrospinning machine to absorb the polyketone spinning solution, discharge the bubbles inside and install a 20-gauge needle, place it on the booster, and the receiving distance from the syringe needle tip to the roller is 15 cm. Start spinning under the conditions of a translation speed of 100 mm / min, a push speed of 0.5 to 2 mL / h, a positive voltage of 7 kV, a negative voltage of -3 kV, a roller speed of 120 r / min, a temperature of 10 to 50 ° C, and a relative humidity of ≥70%, and stop when the solution in the syringe is consumed.
[0038] (3) dissolving tris(hydroxymethyl)aminomethane in deionized water, adding 1 mol / L hydrochloric acid solution to adjust the pH to 8.5, then placing the polyketone nanofiber membrane, placing it on a shaker at 120 r / min for immersion reaction for 12 h, and after the reaction is completed, taking out the membrane and placing it in an oven at 70-100° C. for drying for more than 3 h to obtain a polydopamine-modified polyketone nanofiber membrane;
[0039] The mass ratio of deionized water to tris(hydroxymethyl)aminomethane is 1:(0.001-0.01); and the mass ratio of polyketone to tris(hydroxymethyl)aminomethane in step (1) is 1:(0.5-1.5).
[0040] (4) dissolving silver nitrate in deionized water, adding ammonia water to react, stopping the addition after the solution changes from clear to reddish brown and then to clear, then placing the polydopamine-modified polyketone nanofiber membrane, placing it on a shaker at 80 r / min and soaking it for 5 hours, then dropping an appropriate amount of 2 mol / L NaOH solution and 2 mol / L glucose solution and continuing the reaction for 0.5 to 3 hours. After the reaction is completed, taking out the membrane and placing it in an oven at 70 to 100° C. to dry for more than 3 hours to obtain a modified polyketone nanofiber membrane loaded with silver nanoparticles;
[0041] Among them, the mass ratio of deionized water to silver nitrate is 1:(0.01-0.05); the mass ratio of silver nitrate to NaOH is 1:(0.2-0.5); the mass ratio of silver nitrate to glucose is 1:(2-5); and the mass ratio of polyketone to silver nanoparticles in step (1) is 1:(1-5).
[0042] (5) placing polypropylene pellets into a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm, and hot pressing the film on a flat vulcanizer. The hot pressing conditions are: hot pressing temperature of 190° C., hot pressing time of 10 min, hot pressing pressure of 10 MPa, and then cold pressing at room temperature for 5 min under a pressure of 10 MPa;
[0043] Wherein, the mass ratio of the polypropylene pellets to the polyketone in step (1) is 1:(0.05-0.15);
[0044] The polypropylene pellets are polypropylene resins for films, with a number average molecular weight of 50,000 to 150,000 g / mol, a melting point of 162 to 168° C., and a melt flow index of 2.8 to 30 g / 10 min (230° C. / 2.16 kg).
[0045] (6) stacking the modified polyketone nanofiber membrane loaded with silver nanoparticles and the polypropylene membrane together, and then placing them in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm, and preparing a polypropylene composite membrane by hot pressing molding on a flat vulcanizer, the hot pressing conditions being: hot pressing temperature of 180 to 200° C., hot pressing time of 8 to 15 min, hot pressing pressure of 5 to 10 MPa, and then cold pressing at room temperature for 3 to 10 min under a pressure of 5 to 10 MPa;
[0046] The mass ratio of the polypropylene membrane to the modified polyketone nanofiber membrane loaded with silver nanoparticles is 1:(0.01-0.9).
[0047] The technical solution and effects of the present invention are further illustrated below through practical examples.
[0048] Example
[0049] 1. Preparation of polypropylene composite film
[0050] 1. Some of the reagents used in the embodiments and comparative examples of the present invention are described as follows:
[0051] Polypropylene 1#: PP, L5D98, Guoneng Baotou Coal Chemical Co., Ltd.;
[0052] Polypropylene 2#: PP, T98G, PetroChina Dushanzi Petrochemical Company;
[0053] Polyketone 1#: PK, M630A, number average molecular weight 100,000 g / mol, Hyosung Corporation, Korea;
[0054] Polyketone 2#: PK, M930A, number average molecular weight 60,000 g / mol, Hyosung Corporation, Korea;
[0055] Dopamine: DA, commercially available;
[0056] Sodium chloride: NaCl, commercially available;
[0057] Hydrochloric acid: HCl, commercially available;
[0058] Hexafluoroisopropanol: HFIP, commercially available;
[0059] Dichloromethane: DCM, commercially available;
[0060] Silver nitrate: AgNO 3 , commercially available;
[0061] Tris(hydroxymethyl)aminomethane: Tris, commercially available;
[0062] Glucose: GLU, commercially available;
[0063] Nano silver powder: particle size 20nm, purity not less than 99.9%, commercially available.
[0064] 2. Preparation of polypropylene composite membrane materials in Examples 1 to 10
[0065] (1) This embodiment provides a series of antistatic and antibacterial polypropylene composite film materials, the raw material ratios of which are shown in Table 1.
[0066] Table 1 Raw material ratio of Examples 1 to 10 (weight of polypropylene is 6 g)
[0067] 1 2 3 4 5 6 7 8 9 10 PP1# 100 - 100 100 100 100 100 100 100 100 PP2# - 100 - - - - - - - - PK1# 10 10 8 12 10 10 10 10 10 10 DA 1 1 1 1 0.5 1.5 1 1 1 1 Tris 8 8 8 8 8 8 8 8 8 8 NaCl 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 HFIP 60 60 60 60 60 60 140 50 60 60 DCM 140 140 140 140 140 140 60 150 140 140 <![CDATA[AgNO 3 ]]> 50 50 50 50 50 50 50 50 25 75
[0068] (2) The polypropylene composite film material in Examples 1 to 10 of the present invention is prepared by the following process:
[0069] 1) After HFIP and DCM are prepared into a mixed solvent in proportion, a certain amount of PK, DA and NaCl are dissolved in the mixed solvent in sequence, and the mixture is fully stirred at room temperature in a sealed state until PK is completely dissolved, and then allowed to stand to obtain an electrospinning solution;
[0070] 2) Use the syringe of the electrospinning machine to absorb the PK spinning solution, discharge the bubbles inside, install a 20-gauge needle, and place it on the booster. The receiving distance from the syringe needle tip to the drum is 15 cm. Start spinning at a translation speed of 100 mm / min, a push speed of 1 mL / h, a positive voltage of 7 kV, a negative voltage of -3 kV, a drum speed of 120 r / min, a temperature of 30 ° C, and a relative humidity of 80%. After spinning, remove the spun PK nanofiber membrane from the drum together with the silicone oil paper, place it for 1 hour, remove the PK nanofiber membrane from the silicone oil paper, put it in a plate, and transfer it to an oven to dry at 100 ° C for 12 hours;
[0071] 3) Add Tris to 250 mL of deionized water, stir at room temperature until completely dissolved, and adjust the pH value of the solution to 8.5 using 1 mol / L HCl solution. Soak the PK nanofiber membrane in the solution, place it on a shaker, and react at 120 r / min for 12 hours. After the reaction, take out the membrane and dry it in a 70°C oven for 3 hours to obtain a PDA-modified PK nanofiber membrane;
[0072] 4) Take AgNO 3 Put it into 150mL of deionized water, stir at room temperature until it is completely dissolved, then add ammonia water to the solution, and stop adding when the solution changes from clear to reddish brown and then to clear. Soak the modified PK nanofiber membrane in the solution, place it on a shaker, and run it at 80r / min for 5h. Then add 10mL of 2mol / LNaOH solution, and then add 20mL of 2mol / L glucose solution, and continue the reaction for 0.5h after the addition is completed. After the reaction is completed, take out the membrane, and then put it in a 70℃ oven to dry for 3h to obtain a modified PK electrospun membrane loaded with silver nanoparticles;
[0073] 5) Put the PP pellets into a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm, and heat press them into films using a flat vulcanizer. The hot pressing conditions are: hot pressing temperature 190°C, hot pressing time 10 min, hot pressing pressure 10 MPa, and then cold pressing at room temperature for 5 min under a pressure of 10 MPa;
[0074] 6) The modified PK electrospun membrane loaded with silver nanoparticles and the PP membrane were stacked together, and then placed in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm, and a polypropylene composite membrane was prepared by hot pressing molding on a flat vulcanizer. The hot pressing conditions were: hot pressing temperature of 190°C, hot pressing time of 10 min, hot pressing pressure of 5 MPa, and then cold pressing at room temperature for 5 min under a pressure of 5 MPa.
[0075] 3. Preparation of polypropylene composite film materials in Comparative Examples 1 to 7
[0076] Comparative Example 1
[0077] 6 g of polypropylene 1# pellets were placed in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm, and hot-pressed into a film using a flat-bed vulcanizer. The hot-pressing conditions were: hot-pressing temperature 190°C, hot-pressing time 10 min, hot-pressing pressure 10 MPa, and then cold-pressed at room temperature under a pressure of 10 MPa for 5 min before taking out.
[0078] Comparative Example 2
[0079] (1) After 3.6 g HFIP and 8.4 g DCM are prepared into a mixed solvent, 0.6 g polyketone 1#, 2 g nano silver powder and 6 mg NaCl are added to the mixed solvent in sequence, and the mixture is fully stirred at room temperature in a sealed state until PK is completely dissolved. The solution is dispersed using an ultrasonic cell crusher, the ultrasonic time is 10 min, the ultrasonic power is 100 W, and the temperature is not greater than 50° C., and then cast on a glass plate to form a film. After being placed at room temperature for 12 h, the film is transferred to an oven and dried at 60° C. for 6 h to obtain an Ag / PK composite film;
[0080] (2) The remaining steps are the same as steps 5-6 of Example 1).
[0081] Comparative Example 3
[0082] (1) After 3.6 g HFIP and 8.4 g DCM were prepared into a mixed solvent, 0.6 g polyketone 1#, 0.06 g DA and 6 mg NaCl were dissolved in the mixed solvent in sequence, and the mixture was fully stirred at room temperature in a sealed state until PK was completely dissolved, and then cast on a glass plate to form a film. After being placed at room temperature for 12 h, the film was transferred to an oven and dried at 60° C. for 6 h to obtain a PK film;
[0083] (2) The remaining steps are the same as steps 3 to 6 of Example 1).
[0084] Comparative Example 4
[0085] (1) Same as steps 1 to 5 of Example 1;
[0086] (2) The modified polyketone electrospun membrane loaded with silver nanoparticles and the polypropylene membrane were stacked together and then placed in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm. The polypropylene composite membrane was prepared by hot pressing on a flat vulcanizer. The hot pressing conditions were: hot pressing temperature of 170°C, hot pressing time of 10 min, hot pressing pressure of 5 MPa, and then cold pressing at room temperature for 5 min at a pressure of 5 MPa.
[0087] Comparative Example 5
[0088] (1) Same as steps 1 to 5 of Example 1;
[0089] (2) The modified polyketone electrospun membrane loaded with silver nanoparticles and the polypropylene membrane were stacked together and then placed in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm. The polypropylene composite membrane was prepared by hot pressing on a flat vulcanizer. The hot pressing conditions were: hot pressing temperature of 210°C, hot pressing time of 10 min, hot pressing pressure of 5 MPa, and then cold pressing at room temperature for 5 min at a pressure of 5 MPa.
[0090] Comparative Example 6
[0091] (1) Polyketone 2# was used, and the remaining steps were the same as steps 1 to 6 of Example 1).
[0092] Comparative Example 7
[0093] (1) Same as steps 1 to 4 of Example 1;
[0094] (2) 6 g of PP pellets were divided into two equal parts, and each part was placed in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.1 mm. The two parts were hot-pressed into two PP films using a flat-plate vulcanizer. The hot-pressing conditions were as follows: hot-pressing temperature of 190°C, hot-pressing time of 10 min, hot-pressing pressure of 10 MPa, and then cold-pressed at room temperature for 5 min under a pressure of 10 MPa.
[0095] (3) The modified PK electrospun membrane loaded with Ag nanoparticles was placed between the two PP films mentioned above, and then placed together in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm. The polypropylene composite membrane was prepared by hot pressing on a flat vulcanizer. The hot pressing conditions were: hot pressing temperature 190 °C, hot pressing time 10 min, hot pressing pressure 5 MPa, and then cold pressing at room temperature for 5 min under a pressure of 5 MPa.
[0096] 2. Performance testing of polypropylene composite film
[0097] 1. Taking Example 1 as an example, the antistatic and antibacterial polypropylene composite film material prepared by the method of the present invention was tested, and the results are as follows: Figures 1 to 3 shown.
[0098] Figure 1 This is a SEM image of the modified polyketone electrospun membrane loaded with silver nanoparticles in Example 1. As can be seen from the figure, the silver nanoparticles are tightly coated on the fiber surface of the polyketone nanofiber membrane.
[0099] Figure 2 The SEM energy spectrum scanning images of the modified polyketone electrospun membrane loaded with silver nanoparticles in Example 1, wherein (a) is an element distribution overlay; (b) is a secondary electron image; (c) is the Ag element distribution; (d) is the C element distribution; (e) is the O element distribution. From the element distribution in the figure, it can be seen that the silver nanoparticles are evenly distributed on the fiber surface of the PK electrospun membrane, which can significantly improve the conductivity and antibacterial properties of the PK electrospun membrane.
[0100] Figure 3 The SEM image of the cross section of the antistatic and antibacterial polypropylene composite film prepared in Example 1. As can be seen from the figure, the interface between the upper dense PK film loaded with silver nanoparticles and the lower polypropylene film is tightly bonded, which helps to enhance the impact resistance and wear resistance of the PK film layer and prolong the time for the polypropylene composite film to play its antibacterial and antistatic effects.
[0101] 2. The composite membrane was sampled and tested for corresponding performance. The testing methods of the embodiments of the present invention and the comparative examples are as follows:
[0102] Oxygen permeability: Refer to GB / T 1038-2000 test;
[0103] Antibacterial performance: Tested in accordance with GB / T 31402-2023;
[0104] Antistatic performance: Refer to GB / T 1410-2006 test;
[0105] Pendulum impact resistance: Refer to GB / T 8809-2015 test.
[0106] The properties of the polypropylene materials provided in the embodiments and comparative examples were tested according to the aforementioned performance testing method. The results are shown in Table 2.
[0107] Table 2 Performance test results of polypropylene materials provided by Examples 1 to 10 and Comparative Examples 1 to 7
[0108]
[0109] It can be seen from the above test results that in Examples 1 to 10, the polypropylene composite film material prepared by hot pressing the PK nanofiber film loaded with Ag nanoparticles prepared by a specific electrospinning process and the PP film under strictly limited conditions has good antibacterial and antistatic functions, while maintaining good barrier properties and impact resistance. Compared with the pure PP film material in Comparative Example 1, the oxygen permeability has been significantly reduced, the impact toughness has increased, and more importantly, it has good antibacterial and antistatic properties; Comparative Example 2 directly adds nanosilver powder to PK for film casting, and then superimposes it with the PP film for hot pressing. Since most of the Ag nanoparticles are distributed inside the PK, the antibacterial property is poor, and the interface strength between the PK film and the PP matrix is low, so the impact toughness is poor; in Comparative Example 3, although the Ag nanoparticles are grown on the surface of the PK cast film, the PK cast film loaded with Ag nanoparticles is superimposed with the PP film for hot pressing. However, due to the small specific surface area of the PK film, the loaded Ag nanoparticles are not many, so the antibacterial property is poor, and the interface strength between the PK film and the PP matrix is not high, and the impact toughness is poor; Comparative Examples 4 and 5 do not use limited hot pressing conditions. The former does not form a dense PK film layer due to the low temperature, resulting in poor oxygen permeability and impact toughness. The latter is due to the high temperature, which causes the PK electrospun film to shrink violently during hot pressing, and the PP melt wraps a large number of Ag nanoparticles, so the barrier, antibacterial and electrical conductivity are poor; in Comparative Example 6, due to the use of low molecular weight PK, the PK electrospun film has poor spinnability, a small amount of loaded silver, and it is difficult to form a dense PK film during hot pressing, so that the barrier, antibacterial and electrical conductivity of the PP composite film are limited; in Comparative Example 7, the PK electrospun film loaded with Ag nanoparticles is sandwiched between two layers of PP film for hot pressing. Although the dense PK film formed makes the composite film have better barrier and impact toughness, the antibacterial and antistatic effects are difficult to manifest because the Ag nanoparticles are completely covered by PP.
[0110] From the above, it can be seen that a polypropylene composite film material is obtained by hot-pressing a PK nanofiber membrane loaded with silver nanoparticles and a PP membrane under strictly defined conditions. The PK nanofiber membrane prepared by a specific electrospinning process has the advantages of high specific surface area and strong adsorption, and can achieve a firm load and uniform dispersion of silver nanoparticles on the PK membrane, while giving the composite membrane good antibacterial properties and antistatic properties. Under strictly defined hot pressing conditions, the PK electrospun membrane forms a dense PK membrane, which has excellent barrier properties and is tightly bonded to the interface between the PP layers, significantly improving the barrier properties and impact toughness of the PP composite film material, and finally obtaining a polypropylene composite film material with excellent antibacterial, barrier, impact resistance and antistatic properties.
Claims
1. A method for preparing an antistatic and antibacterial polypropylene composite film material, characterized in that: The steps include: a. preparing a polyketone spinning solution and obtaining a polyketone nanofiber membrane by electrospinning; b. using polydopamine and silver nitrate to modify the polyketone nanofiber membrane to obtain a modified polyketone nanofiber membrane loaded with silver nanoparticles; c. Place the polypropylene pellets into the mold frame and heat press them into a polypropylene film; d. The modified polyketone nanofiber membrane loaded with silver nanoparticles is stacked on the polypropylene film, and then placed together in a mold frame, hot pressed at 180-200°C under a pressure of 5-10 MPa for 8-15 min, and then cold pressed at room temperature under a pressure of 5-10 MPa for 3-10 min, and then taken out to obtain an antistatic and antibacterial polypropylene composite membrane material.
2. The method for preparing the antistatic and antibacterial polypropylene composite film material according to claim 1, characterized in that: In step a, hexafluoroisopropanol and dichloromethane are prepared into a mixed solvent in proportion, polyketone, dopamine and sodium chloride are added in sequence, the mixture is sealed and fully stirred at room temperature until the polyketone is completely dissolved, and the mixture is allowed to stand to obtain a polyketone spinning solution; Among them, the mass ratio of hexafluoroisopropanol and dichloromethane in the mixed solvent is 1:(0.25-4); the mass ratio of polyketone and the mixed solvent is 1:(10-50); the mass ratio of polyketone and dopamine is 1:(0.05-0.2); the mass ratio of polyketone and sodium chloride is 1:(0.005-0.02).
3. The method for preparing the antistatic and antibacterial polypropylene composite film material according to claim 2, characterized in that: The polyketone is an aliphatic polyketone, which is a linear alternating copolymer synthesized from carbon monoxide, ethylene and propylene, and has a number average molecular weight of 90,000 to 120,000 g / mol.
4. The method for preparing the antistatic and antibacterial polypropylene composite film material according to claim 1, characterized in that: In step b, the modification method is specifically: b1. The tris(hydroxymethyl)aminomethane was dissolved in deionized water, and hydrochloric acid solution was added to adjust the pH to 8.5, and then the polyketone nanofiber membrane was fully immersed in the reaction. After the reaction was completed, the membrane was removed and dried to obtain a polydopamine-modified polyketone nanofiber membrane; b2. Dissolve silver nitrate in deionized water, add ammonia water for sufficient reaction, then put in the polydopamine-modified polyketone nanofiber membrane and soak it thoroughly, then add appropriate amount of NaOH solution and glucose solution to continue the reaction. After the reaction is completed, take out the membrane and dry it to obtain a modified polyketone nanofiber membrane loaded with silver nanoparticles.
5. The method for preparing the antistatic and antibacterial polypropylene composite film material according to claim 4, characterized in that: In step b2, the mass ratio of deionized water to silver nitrate is 1:(0.01-0.05); ammonia water is added dropwise for sufficient reaction, and the addition is stopped after the solution changes from clear to reddish brown and then to clear; the mass ratio of silver nitrate to NaOH is 1:(0.2-0.5); the mass ratio of silver nitrate to glucose is 1:(2-5); the mass ratio of polyketone to silver nanoparticles in step a is 1:(1-5).
6. The method for preparing the antistatic and antibacterial polypropylene composite film material according to claim 1, characterized in that: In step c, the mold frame is a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm; the mass ratio of the polypropylene pellets to the polyketone in step a is 1:(0.05-0.15).
7. The method for preparing the antistatic and antibacterial polypropylene composite film material according to claim 6, characterized in that: The polypropylene pellets are polypropylene resins for films, and have a number average molecular weight of 50,000 to 150,000 g / mol, a melting point of 162 to 168° C., and a melt flow index of 2.8 to 30 g / 10 min (230° C. / 2.16 kg).
8. The method for preparing the antistatic and antibacterial polypropylene composite film material according to claim 1, characterized in that: In step d, the mold frame is a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm; the mass ratio of the polypropylene film to the modified polyketone nanofiber membrane loaded with silver nanoparticles is 1:(0.01-0.9).
9. Antistatic and antibacterial polypropylene composite film material, characterized by: The method is prepared according to any one of claims 1 to 8.